P09.06.B The effectiveness of antiepileptic drug tripletherapy in refractory epileptic glioma patients: a multicenter observational cohort study. (5th September 2022) - van der Meer, P B; Dirven, L; Fiocco, M; Vos, M J; Kouwenhoven, M C M; van den Bent, M J; Taphoorn, M J B; Koekkoek, J A F
Abstract: Background: About 10% of the glioma patients need antiepileptic drug (AED) tripletherapy due to refractory epilepsy. This study aimed to determine whether levetiracetam combined with valproic acid and clobazam (LEV+VPA+CLB), a commonly prescribed tripletherapy, has favourable effectiveness compared to other tripletherapy combinations in glioma patients. Material and Methods: In this multicenter retrospective observational cohort study, the primary outcome was the cumulative incidence of treatment failure for any reason, from initiation of AED tripletherapy. Secondary outcomes included cumulative incidences of: 1) treatment failure due to uncontrolled seizures; 2) treatment failure due to adverse effects; and 3) recurrent seizure. Maximum duration of follow-up was 36 months. Results: Ninety patients, from an initial cohort of n=1435 patients, received AED tripletherapy after second-line AED duotherapy treatment failure due to uncontrolled seizures. LEV+VPA+CLB was prescribed to 43 (48%) and other AED tripletherapy to 47 (52%) patients. The cumulative incidence of treatment failure for any reason of LEV+VPA+CLB did not significantly differ from other tripletherapy combinations (12 months: 47% [95%CI, 31-62%] versus 42% [95%CI, 27-56%], p=0.892). No statistical significant differences for treatment failure due to uncontrolled seizures (12 months: 12% [95%CI, 4-25%] versus 18% [95%CI, 8-30%], p=0.445), due to adverse effects (12 months: 22% [95%CI, 11-36%] versus 15% [95%CI, 7-27%], p=0.446), or recurrent seizure (1 month: 65% [95%CI, 48-78%] versus 63% [95%CI, 47-75%], p=0.911) were found. Conclusion: LEV+VPA+CLB has not shown favourable efficacy or tolerability compared to other AED tripletherapy combinations in glioma patients. Therefore, we cannot specifically recommend CLB as tripletherapy add-on AED to LEV+VPA.